Neonatal evaluation by extended (12 area) vs. traditional (6 area) lung ultrasound scoring (NEXT-LUS): a prospective observational study - Chetan, Chinmay; Majumder, Shoham; Debnath, Aninda; Kaur, Ravleen; Jaybhaye, Deepak; Kaur, Arshpuneet; Patra, Saikat (Frontiers in Pediatrics, 2025)
BackgroundLung ultrasound (LUS) offers a safe, repeatable, radiation-free tool in management of respiratory distress in neonates. Despite wide use, limited data exists on optimal scoring approaches.MethodologyA prospective observational study was conducted over 6 months in a tertiary neonatal intensive care unit (NICU) enrolling neonates with respiratory distress within 2 h of admission after consent. LUS was performed using both 6-area and 12-area scanning approaches. Scores were assigned per Brat's criteria. Primary outcome was prediction of need for invasive ventilation within 72 h. Secondary outcomes included optimal cut-off scores, correlation with clinical outcomes and procedural safety.ResultsAmong 73 neonates enrolled, the 6-area LUS score (cut-off ≥5) predicted invasive mechanical ventilation within 72 h with 75% sensitivity and 67% specificity (AUC = 0.76). The 12-area score (cut-off ≥13) had similar accuracy (sensitivity 75%, specificity 73%; AUC = 0.77). Both 6-area and 12-area scores performed better in neonates <34 weeks (AUCs: 0.83 vs. 0.86). In neonates presenting after 24 h of life (n = 19), both scores maintained good accuracy (AUCs: 0.80 for 6-area, 0.83 for 12-area). Multivariate analysis identified partial pressure of carbon dioxide (pCO2) and duration of stay as independent predictors. The 12-area score required reattempts (in 9% cases) unlike the 6-area score.ConclusionIn neonates presenting with respiratory distress, 6-area and 12-area LUS scores done within 2 h of admission show good and comparable predictive value regarding need for invasive ventilation by 72 h.